IMPLEMENTATION OF A WEB-BASED VALUE MANAGEMENT INFORMATION SYSTEM AS AN EFFORT TO DIGITALIZE THE ACADEMIC SECTOR - Hartatik Hartatik (International Journal of Multidisciplinary Research and Literature, 2022)
The research was conducted in the implementation of a web-based Achievement management information system, where in this system there are 3 actors, namely admin, teacher and principal. The admin actor is in charge of managing data for teachers, students, classes, subjects, grades, extracurriculars, OSN and a list of recommendations for students with academic and non-academic achievements. In the homeroom teacher actor manages student data and grades and prints report cards. While the principal actor can see data on teachers, classes and subjects. With this system, it is hoped that it will make it easier to manage report cards and achievements. Then the homeroom teacher can only enter the grades of students who are only in their class. Subject teachers do not need to test students or assess students manually because the system will recommend students based on subject scores from daily grades, UTS and UAS with a weighted score according to the requirements that have been determined by the school. For extracurricular activities supervisors, there is also no need to test students one by one because the system will recommend students based on several aspects of predetermined values ​​for students to represent the school in non-academic competitions such as pencak silat, volleyball, basketball and others. After that the system can automatically recommend students to represent the school in academic (OSN) and non-academic competitions, according to the provisions of the competition criteria held with report cards and student skill scores